The Implementation of the Indonesian Ulema Council's Fatwa on the Prohibition of Smoking in Brebes District from the Istishan Perspective - Naqiyyatussa’diyah, Naqiyyatussa’diyah; Hidayati, Manzilah Nuri; Saiban, Kasuwi (Al-Bayyinah, 2025)
This research aims to explore the implementation of the fatwa of the Indonesian Ulema Council (MUI) regarding the prohibition of smoking through an istihsan approach. The istihsan approach as a method for determining Islamic law is used to understand how the flexibility of Sharia can be applied in diverse social and cultural contexts. This research is a field study, where data is obtained from events that occur in the field as they are. The sample in this study is alumni of the Integrated Islamic Elementary School Harum Brebes, serving as the object or case study. Data collection was conducted through interviews with alumni of Integrated Islamic Elementary School Harum Brebes, followed by analyzing and interpreting what was. The findings of this study indicate the dynamics of understanding and attitudes of alumni towards the fatwa, as well as how the values of public interest are interpreted in everyday life practices. The main contribution of this research lies in strengthening the perspective of istihsan as an alternative approach in bridging the gap between Islamic legal norms and social realities, especially on contemporary issues such as smoking. This study is expected to serve as a reference for policymakers, educational institutions, and religious authorities in formulating more contextual and effective strategies for implementing fatwas.